Leveraging the promotion of tourist destinations and the interpretation of their heritage using virtual reality - Cunha, Carlos R. (2022)
Technology is increasingly a transversal layer to all activities and, in this sense, exploring the potential of technology as a driver to support the competitiveness of organizations and nations has become a necessity for survival. Tourism is a fundamental asset in many modern economies and certainly fundamental from a civilizational and generational point of view, insofar as associated with a wide range of tourist destinations is its heritage. As such, the promotion and interpretation of destinations and their heritage are very important and, in these areas, technologies have played a fundamental and revolutionary role. In this scenario, Virtual Reality, among other technologies, demonstrates a vast potential in promoting tourist destinations and in creating immersive experiences that allow for a better interpretation of destinations and their heritage, as well as greater attractiveness for younger generations. This article, after a review of technological concepts and a discussion of their role in the context of tourism and heritage, proposes a conceptual model capable of contributing to a more agile and massified creation of Virtual Reality experiences. Finally, an experimental prototype created for an olive and olive-oil museum is presented, with the aim of facilitating the interpretation, by visitors, of its permanent exhibition objects and improving the visiting experience.